FACEBOOK SEBAGAI MEDIA DAKWAH ISLAM - Achmad Syarifudin (Fakultas Dakwah dan Komunikasi, Universitas Islam Negeri, Raden Fatah Palembang, 2014)
This article discusses the position of social media as new media in communications and information technology in the development of preaching Islam or dakwah Islamiyah. Facebook as social media that is very far-reaching into a very good medium to spread the teachings of Islam. In the new media many other aspects of interest to serve as a medium of propaganda for example MP 3, DVD, e-mail, e-Book, applications mobile, live streaming, etc., but facebook is seen representing these media because social networking is very familiar to users in cyberspace. Most important is the content of facebook it should load side of goodness and teachings of Islamic, either in the form of statements, pictures and video.